Estimation and Comparison of Serum Levels of Sodium, Potassium, Calcium and Phosphorus in Different Stages of Chronic Kidney Disease - Poudel, Bibek; Mittal, Ankush; Yadav, Binod Kumar; Sharma, Prakriti; Jha, Bharat; Raut, Kanak Bahadur (Nepal Journal of Epidemiology, 2011)
Background: Chronic Kidney Disease (CKD) is a worldwide growing issue and a public health problem. It is associated with significant morbidity and mortality. The prevalence of CKD has been described in several studies. High prevalence of CKD has also reported in the different studies from different part of world. The prevalence of reduced glomerular filtration rate (GFR) in Australia was 11.2%. Singapore, a South-East Asian country, reported a CKD prevalence of 10.1%, while the prevalence of CKD in Japanese general population was reported to be 18.7%. Reduced kidney function is associated with a variety of biochemical abnormalities such as electrolytes. However, the extent of the changes and their magnitude in relation to different stages of CKD is not well defined especially in the early stages of CKD. Thus, the main objective of our study was to assess the variations in the serum levels of sodium, potassium, calcium and phosphorus in different stages of CKD. Materials and methods: It was a hospital based cross-sectional study conducted in the Department of Clinical Biochemistry in collaboration with the Department of Internal Medicine (nephrology unit), Kathmandu, Nepal between 1st February, 2008 to 1st January, 2010. CKD was defined as per National Kidney Foundation Guidelines. The variables collected were age, gender, blood pressure, serum level of urea, creatinine , sodium, potassium, calcium, phosphorus, urinary albumin, urinary total protein (UTP), urinary protein creatinine ratio (PCR). The One way ANOVA was used to examine the statistical significant difference between groups. Correlation of different parameters with markers of CKD was done by Pearson‘s correlation for quantitative data. A p-value of <0.05 (two-tailed) was used to establish statistical significance. Results: Increased values of systolic and diastolic blood pressure found up to the level of stage IV CKD. However, in stage V CKD a slight decrement of blood pressure from stage IV CKD was seen. With the progression of stages of CKD, sodium levels were found to be decreased (p<0.001). In contrast to that potassium and phosphorus levels were found to be increased with the stages of CKD and (p<0.001). Serum level of calcium was found to be declined with the augment in stages of CKD (p<0.001). Positive and negative correlation of different parameters with kidney damage markers was assessed by Pearson’s correlation coefficient. Conclusion: The elevation in serum level of potassium, phosphorus and decrease in serum level of calcium were obvious even among the patients with early stages CKD. DOI: http://dx.doi.org/10.3126/nje.v1i5.6154 Nepal Journal of Epidemiology 2011;1 (5):160-167